EVALUATION OF THE EFFICIENCY OF BROADLEAF WEED HERBICIDES AT DIFFERENT PLANTING DISTANCES ON WHEAT CROP - Hayawi , Jassim, A. Hayawi; Al-Mafrajy, A. S. H. Al-Mafrajy; Muhammad, A.W. Taha (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
This study was aimed to evaluation of broad leaf herbicide season 2022/2023 at this research included two factors, the first: weed pesticides with four levels (control, 2, 4-D, Cranstar and Lintor) and with the recommended concentrations for each herbicide. The second: planting distances: which are 15 and 30 cm between the lines. The research was carried out using within factorial experiments complete randomized block design (RCBD), sowing took place on 11/15/2022, with a seeding rate of (100) kg . h-1 for Sham 6 cultivar, the herbicides were sprayed by a dorsal sprayer with a capacity of 16 liters on 11/2/2023, and on 3/25/2023 the weed characteristics were studied, and on 5/27/2023 the yield characteristics were studied and the obtained results were summarized as follows: Significant increases in the number of broad weeds, fresh and dry weight of broadleaf weeds at a distance of 30 cm between lines compared with a distance of 15 cm. The distance 30 cm significantly increased the characteristics of plant height and spike length compared with the distance 15 cm. A significant increases in grain yield occurred at the distance 15 cm between the lines compared to the distance 30 cm. The herbicides achieved a significant decreases in the number of broadleaf weeds and their fresh and dry weight compared with the control treatment.